2006
DOI: 10.1002/ddr.20077
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes and health‐related quality of life in effectiveness studies: pros and cons

Abstract: The importance of patient perspectives on disease impact and response to therapy is increasingly recognized. Patient-reported outcomes (PROs), including health-related quality of life (HRQL), provide information on the effectiveness of medical interventions that cannot be obtained using objective clinical measures. For drug development, PROs such as symptom questionnaires are accepted by the European Medicines Agency (EMEA) and US Food and Drug Administration (FDA) in the approval process. HRQL assessments can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 68 publications
2
32
0
Order By: Relevance
“…Despite the agreement on symptoms with highest prevalence rates (i.e., joint pain, vasomotor symptoms, loss of interest in sexual intercourse) pivotal trials report significantly lower rates [3,4]. Our results, thereby, confirm the presumption that PROs reveal a higher level of symptom burden than conventional pivotal clinical trials [11,12,25,26]. Ruhstaller et al [16] reported comparable results in their PRO-based study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite the agreement on symptoms with highest prevalence rates (i.e., joint pain, vasomotor symptoms, loss of interest in sexual intercourse) pivotal trials report significantly lower rates [3,4]. Our results, thereby, confirm the presumption that PROs reveal a higher level of symptom burden than conventional pivotal clinical trials [11,12,25,26]. Ruhstaller et al [16] reported comparable results in their PRO-based study.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding clinical practice, our findings emphasize the necessity of increased application of self-report instruments given that outcomes voiced by the patients provide essential information on treatment impact (e.g., pain intensity and pain relief) that are difficult to obtain from other sources [26]. Screening for self-reported data could minimize potential negative consequences of the patient attitudes toward their physician and/or symptom experience and could help identify the patients suffering from side-effects otherwise missed.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to clinical measures, patient-reported outcomes (PROs) are important to understand the patient's perspective of disease (4,5). Most PROs used in clinical trials of psoriasis therapies, such as the Dermatology Life Quality Index (DLQI) (6) and Short Form 36 v2 Acute Health Survey (SF-36v2), assess the impact of psoriasis or illness in general on health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…It is a promising tool for use in large reallife studies, epidemiological and phase IV studies, as well as in clinical practice. 7,40,47,48 However, further validation in specifi c studies is needed.…”
Section: Sexual Life Impactmentioning
confidence: 99%